Đặc điểm trầm tích và xu thế phát triển bãi bồi Kim Sơn (Ninh Bình) - Hoài, Vũ Thị Thu; Huyên, Nguyễn Xuân (Vietnam Journal of Earth Sciences, 2009)
Material and sedimentation characteristics of the Kim Son alluvial ground (Ninh Binh) ...